Reliability of pulse palpation in the detection of atrial fibrillation in an elderly population - Jaakkola J; Vasankari T; Virtanen R; Airaksinen KEJ (TAYLOR & FRANCIS LTD, 2022)
Purpose: Atrial fibrillation (AF) may first present as an ischemic stroke. Pulse palpation is a potential screening method for asymptomatic AF. We aimed to assess the reliability of pulse palpation by the elderly in detecting AF.Materials and methods: After brief information and training session conducted by a nurse, 173 subjects aged 75 years were instructed to palpate their pulse regularly for a month. After this, their ability to distinguish sinus rhythm (SR), SR with premature ventricular contractions (PVC) and AF by pulse palpation was assessed using an anatomic human arm model programmable with various rhythms. A control group of 57 healthcare professionals received the same information but not the training. Subjects unable to find the pulse were excluded (25 (14.5%) of the elderly and none in the healthcare group).Results: The median age of the elderly subjects was 78.4 [3.9] years and 98 (56.6%) were women. There were no differences between the elderly and healthcare groups in detecting SR (97.3% vs. 96.5%) or SR with PVCs (74.3% vs. 71.4%), but the elderly subjects identified slow (81.8% vs. 56.1%) and fast AF (91.9% vs. 80.7%) significantly better than the healthcare group. The ability to recognize SR with PVCs by the elderly was independently predicted by previous pulse palpation experience, secondary or higher level of education and one-point increase in MMSE score, while identifying the other rhythms had no predictors.Conclusions: The elderly can learn to reliably distinguish a normal rhythm after education. Pulse self-palpation may be a useful low-cost method to screen for asymptomatic AF.